Evaluation of Lead (Pb) Bioaccumulation Levels by sea grass (Enhalus acoroides) at Tulehu Village Port - Mariwy, Abraham; Manuhutu, Julita B.; Tuhalauruw, Debby E. (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2025)
This research aims to study the level of heavy metal Pb bioaccumulation by sea grass (Enhalus acoroides) in the waters of Tulehu Village, Central Maluku Regency, where the type of particles and Pb content in sediment, roots and leaves are important variables for studying the accumulation and translocation of Pb metal ions by sea grass. Lead (Pb) content in sediment, roots and leaves of sea grass was measured using an atomic absorption spectrophotometer. The ability to accumulate and translocate lead (Pb) in sea grass (Enhalus acoroides) is known from the BCF (bioconcentration factor) and TF (translocation factor) values. The results of the study showed that the type of sediment particle grains at point I was 2.92% gravel, 86.67% sand, 26.67% mud, the size of sediment grains at point II was 16.67% gravel, 82.94% sand, 2.35% mud, and the size of sediment grains at point III was 19.77%, 64.58% sand, 1.04% mud. The Pb metal content produced at point I ranged from 4.80 mg/kg, point II ranged from 4.85 mg/kg and point III ranged from 4.44 mg/kg. The BCF values obtained at points I, II, and III were respectively 0.55; 2.20; 2.12.